2016
DOI: 10.1039/c6cc05222c
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral ligands as electron storage reservoirs and their role in enhancement of photocatalytic hydrogen generation

Abstract: The contrasting early-time photodynamics of two related Ru/Pt photocatalysts with very different photocatalytic H2 generation capabilities are reported. Ultrafast equilibration (535 ± 17 fs) creates an electron reservoir on the peripheral ligands of the ester substituted complex, allowing a dramatic increase in photocatalytic performance. This insight opens the way towards a novel design strategy for H2 generating molecular photocatalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 34 publications
5
33
0
Order By: Relevance
“…However, emission data indicate that the emission decays are different for palladium‐ and platinum‐containing complexes, and hence the electron flows in those complexes are also different. In an earlier study, transient‐absorption measurements indicated that the dceb ligands most likely act as an electron store, which is contrary to the traditional assumption that electron density is stored on the bridging ligand . The present contribution supports this perception, based on the obtained experimental and DFT data.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…However, emission data indicate that the emission decays are different for palladium‐ and platinum‐containing complexes, and hence the electron flows in those complexes are also different. In an earlier study, transient‐absorption measurements indicated that the dceb ligands most likely act as an electron store, which is contrary to the traditional assumption that electron density is stored on the bridging ligand . The present contribution supports this perception, based on the obtained experimental and DFT data.…”
Section: Discussionsupporting
confidence: 77%
“…The complexes reported in this contribution are part of a larger investigation of Ru/Pd and Ru/Pt dyads with various bridging (see Figure ) and peripheral ligands performed by our group under the same experimental conditions . As was observed for the compounds investigated in this contribution, the catalytic activity of these dyads in hydrogen evolution was dependent on changes to the bridging or the peripheral ligands.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…However, complex 1 exhibited rather low TON compared to many other supramolecule catalysts, probably due to its shorter emission lifetime. According to the relative reports, the excited state lifetimes of reported bimetallic complexes are usually multiples even ten times of that of 1 , enabling the proceeding of the slow photochemical processes . Additionally, the quenching constant ( k q ) of 1 is about one or two orders of magnitude lower than other systems, indicating some of the difficulties of electron transfer between 1 and sacrificial agent.…”
Section: Figurementioning
confidence: 99%